Atypical histiocytic granuloma: A differential to nonhealing ulcers of the oral cavity - Shashi Ranjan; Sailesh K Mukul; Rashmi Issar (Wolters Kluwer Medknow Publications, 2014)
This is a case report of a rare clinical entity known as atypical histiocytic granuloma (AHG), which was previously grouped under a broad category known as pseudolymphoma or traumatic eosinophilic granuloma. Less than 15 cases of AHG have been reported until date. AHG poses diagnostic dilemma due to its clinical as well as histopathological appearance where it stimulates malignancy. A proper clinicopathological evaluation is necessary to establish the diagnosis and to avoid overtreatment. In this report, we review previously reported cases in literature and try to establish proper clinicopathological correlation, differential diagnosis and management. These will familiarize clinicians to include AHG in their differential diagnosis as well as for the pathologist to segregate pseudolymphomatous lesion in their proper categories. The role of immunohistochemistry (IHC) has been given prime importance to establish the exact diagnosis. Further in this report, we review different status on lymphoproliferative disorders and advocate the use of IHC in categorizing these lesions upon cell lineage and to establish proper nomenclature for these lesions.